An endophytic bacterial strain, Enterobacter cloacae TMX-6, enhances the degradation of thiamethoxam in rice plants. (April 2021) - Zhan, Honglin; Wan, Qun; Wang, Ya; Cheng, Jiangfeng; Yu, Xiangyang; Ge, Jing
Abstract: Thiamethoxam (TMX) has been widely used over the last two decades. TMX residue in the environment has drawn great public attention. An endophytic bacterial strain, TMX-6, capable of degrading TMX was isolated from wild Ophiopogon japonicus and was identified as Enterobacter cloacae by morphology and 16S ribosomal DNA sequence analysis. After being marked with green fluorescent protein plasmid, TMX-6 was successfully inoculated in the rice plants ( Oryza sativa L.). The numbers of TMX-6 in non-TMX treated rice plants ranged from 3.9 to 4.6 log CFU g −1 in the roots, and from 2.7 to 4.0 log CFU g −1 in the shoots; while ranged from 3.9 to 5.3 log CFU g −1 in roots and from 2.7 to 4.1 log CFU g −1 in shoots of TMX treated rice plants. Nearly 28%, 33%, 77% and 99% of TMX was removed from the hydroponic medium (HM), HM with strain TMX-6, HM with uninoculated rice and HM with inoculated rice, respectively, at the end of a 21-day (d) experiment period, and the correspondent half-lives of TMX were 46.2, 38.5, 9.9 and 4.7 d, respectively. Eleven TMX metabolites were identified in both inoculated and uninoculated rice plants through metabolomics data analysis. The intensity of TMX- NH, TMX-urea and clothianidin increased more than 3 times in inoculated rice plants on day 6. This demonstrates the usefulness of the strain TMX-6 to enhance the degradation of TMX-contaminated substrates and reduce levels of toxic insecticides in crop plants. Highlights: Strain TMX-6 could be inoculated and translocated in rice through roots. TMX-6 enhanced the degradation rate of thiamethoxam in the rice plants. Degradation pathways of thiamethoxam were studied in the rice plants. TMX-6 inoculation enhanced the signal intensity of thiamethoxam metabolites.